Preparation method and application of Fe2O3-Bi4TaO8Br photo-Fenton catalyst

By depositing Fe2O3 on the surface of Bi4TaO8Br nanosheets, the Fe2O3-Bi4TaO8Br heterojunction catalyst is formed, and the existing photofenton catalysts are solved, and efficient photofenton degradation performance and low-cost preparation process are achieved.

CN119869569AActive Publication Date: 2025-04-25KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202510083907.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing photofenton catalysts have problems such as low visible light utilization rate and rapid recombination of photogenerated electron-hole pairs, resulting in high processing costs and limited catalytic performance.

Method used

Fe2O3 was deposited on the surface of Bi4TaO8Br nanosheets by hydrothermal method to form Fe2O3-Bi4TaO8Br heterojunction catalyst, and Bi4TaO8Br nanosheets were prepared by molten salt method to enhance the migration and separation efficiency of photogenerated charges.

Benefits of technology

It achieves efficient photofenton degradation performance, with a degradation rate of 72.57% in 30 minutes. At the same time, the preparation process is simplified, the cost is reduced, and it has good repeatability and industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869569A_ABST
    Figure CN119869569A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Fe2O3-Bi4TaO8Br photo-Fenton catalyst, and belongs to the technical field of advanced oxidation treatment. The specific preparation method comprises the following steps: preparing a Bi4TaO8Br nanosheet by virtue of a molten salt method, and then loading Fe2O3 on the Bi4TaO8Br nanosheet by virtue of a hydrothermal method, so as to obtain the Fe2O3-Bi4TaO8Br photo-Fenton catalyst. The prepared Fe2O3-Bi4TaO8Br photo-Fenton catalyst shows efficient photo-Fenton degradation performance on tetracycline (TC) under the visible light condition, meanwhile, the preparation process is safe, simple, convenient and efficient, and potential environment purification application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a Fe2O3-Bi4TaO8Br photo-Fenton catalyst, belonging to the technical field of advanced oxidation treatment. Background Art

[0002] Photo-Fenton technology, as an advanced oxidation treatment technology, combines the advantages of photocatalysis and Fenton technology. It produces active oxygen species such as hydroxyl radicals through light energy excitation, effectively degrading antibiotic pollutants, and is green and environmentally friendly. However, traditional photo-Fenton technology is limited by the low visible light utilization rate of photocatalysts and the rapid recombination of photogenerated electron-hole pairs, resulting in high treatment costs.

[0003] Currently, many layered bismuth-based compounds have been used as catalysts for environmental remediation, such as Bi m XO n (Bi2O3, Bi2S3, BiVO4, Bi2WO6, Bi2MoO6, Bi4Ti3O 12 and Bi2O2CO3), BiOY (Y=Cl, Br and I), Bi4ZO8Y (Z=Nb and Ta, Y=Cl, Br and I), etc. Among them, bismuth tantalum oxybromide (Bi4TaO8Br) has attracted widespread attention as a Sillen-Aurivilius perovskite phase bismuth-based oxyhalide. Compared with the bulk BiOBr crystal structure, the layered Bi4TaO8Br can expose more reaction sites. [Bi2O2] 2+ and [Br] - The layered structure has a strong built-in electric field perpendicular to each ion layer, which can accelerate the transfer of photoinduced carriers along the

[001] direction. At the same time, the halogen layer consumes the photogenerated holes, thereby improving the separation efficiency of photoinduced carriers and promoting the reaction kinetics. However, the slow charge migration seriously limits the catalytic performance of Bi4TaO8Br, the poor structural and interface carrier separation efficiency, and its limited activity hinders its practical application.

[0004] Existing studies have shown that the coupling of variable-valence metal-based semiconductors (such as Fe, Co, Ni, Cu, Zn and Ce) can not only enhance the light absorption performance, but also activate the Fenton reaction by reacting with H2O2, thereby obtaining excellent degradation performance. Fe2O3 was deposited on the surface of Bi4TaO8Br nanosheets by a hydrothermal method. As a transition metal oxide, Fe2O3 has the advantages of a narrow band gap of 2.20 eV, strong photooxidation, low cost, high conductivity and environmental friendliness, and is a good co-catalyst. In addition, Fe2O3 has a more negative conduction band and valence than Bi4TaO8Br. Fe2O3 was modified on the surface of Bi4TaO8Br nanosheets to prepare a new Fe2O3-Bi4TaO8Br photocatalyst. Summary of the invention

[0005] In order to solve the problems existing in the existing photo-Fenton catalyst, one of the purposes of the present invention is to provide a method for preparing a Fe2O3-Bi4TaO8Br photo-Fenton catalyst, which specifically comprises the following steps:

[0006] (1) Synthesis of BiOBr precursor: Weigh Bi(NO3)3·5H2O and dissolve it in ethylene glycol to obtain solution I; weigh KBr and dissolve it in deionized water to obtain solution II. Solution II is added dropwise to solution I under stirring. After standing, the supernatant is discarded, the precipitate is washed, and dried to obtain BiOBr.

[0007] (2) Preparation of Bi4TaO8Br nanosheets by molten salt method: Ta2O5, Bi2O3 and BiOBr prepared in step (1) were weighed, ground together and put into a crucible for calcination. After calcination, the calcined product was naturally cooled, washed with a centrifuge and dried to obtain Bi4TaO8Br nanosheets.

[0008] (3) Dispersing the Bi4TaO8Br nanosheets prepared in step (2) into anhydrous ethanol, stirring until the Bi4TaO8Br nanosheets and the anhydrous ethanol are fully mixed, and then adding Fe(NO3)3·9H2O while stirring until the Fe(NO3)3·9H2O is completely dissolved to obtain a suspension, subjecting the suspension to hydrothermal treatment, and naturally cooling the suspension to room temperature, separating, washing, drying, and collecting the obtained product to obtain a Fe2O3-Bi4TaO8Br photo-Fenton catalyst.

[0009] Preferably, in step (1), the molar concentration of Bi(NO3)3·5H2O in solution I is 400-420 mmol / L, the molar concentration of KBr in solution II is 400-420 mmol / L, the volume ratio of solution I to solution II is 1:1, and the molar ratio of Bi(NO3)3·5H2O to KBr is 1:1.

[0010] Preferably, the stirring in step (1) is magnetic stirring, the stirring speed is 250-350 r / min, and the stirring temperature is 20-100°C.

[0011] Preferably, in step (2), the molar ratio of Ta2O5, Bi2O3 and BiOBr is (0.2-0.3):(0.7-0.8):(0.4-0.6).

[0012] Preferably, the calcination conditions in step (2) are: 10°C min -1 The temperature was raised to 700 °C at a heating rate of 100 °C and maintained for 14 h.

[0013] Preferably, in step (3), the mass molar ratio of Bi4TaO8Br nanosheets to Fe(NO3)3·9H2O is (0.15-0.25):(1-2), expressed in g:mmol.

[0014] Preferably, the conditions for the hydrothermal treatment in step (3) are: a holding temperature of 80 to 120° C. and a holding time of 5 to 8 hours.

[0015] Preferably, the washing step in step (3) is: washing thoroughly three times with distilled water and anhydrous ethanol respectively.

[0016] Beneficial effects of the present invention

[0017] (1) The present invention synthesizes a novel Fe2O3-Bi4TaO8Br heterojunction catalyst by a hydrothermal method, which broadens the application of bismuth oxybromide-based photo-Fenton. The prepared Fe2O3-Bi4TaO8Br photo-Fenton catalyst combines the efficient oxidation characteristics of the photo-Fenton technology with the excellent photoelectric properties of Bi4TaO8Br nanosheets to form a synergistic composite material.

[0018] (2) The present invention uses a molten salt synthesis method to construct Bi4TaO8Br nanosheets, and uses its internal electric field to provide a strong driving force for the photogenerated charge vector migration between Bi4TaO8Br and Fe2O3. At the same time, due to the formation of Fe-O bonds at the heterojunction interface, the charge flow is accelerated, the charge transfer energy barrier is reduced, and effective charge separation is achieved, showing excellent photo-Fenton degradation performance, with a degradation rate of 72.57% in 30 minutes.

[0019] (3) The present invention grows Fe2O3 on its surface through a simple operation process, which effectively overcomes the shortcomings of Bi4TaO8Br in photogenerated carrier migration and light absorption. It has the advantages of simple method, low cost, good repeatability, etc., and is conducive to industrial application in the field of environmental remediation. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1XRD diffraction patterns of the photo-Fenton catalysts prepared in Examples 1, 2 and Comparative Examples 1, 2 and 3.

[0021] Figure 2 SEM images of the photo-Fenton catalysts prepared in Examples 1, 2 and Comparative Examples 1, 2, and 3.

[0022] Figure 3 This is a comparison chart of the degradation performance of TC by the photo-Fenton catalysts prepared in Examples 1 and 2 and Comparative Examples 1, 2 and 3.

[0023] Figure 4 UV-vis DRS graphs of the photo-Fenton catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0024] Figure 5 This is a stability test diagram of the photo-Fenton catalyst prepared in Example 1.

[0025] Figure 6 This is the EIS performance test of the photo-Fenton catalyst of Example 1 and Comparative Example 2.

[0026] Figure 7 The photo-Fenton catalysts of Example 1 and Comparative Example 2 have a photocurrent response. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0028] Unless otherwise specified, all reagents used in the present invention are of conventional commercially available analytical grade.

[0029] Example 1

[0030] A preparation method of Fe2O3-Bi4TaO8Br photo-Fenton catalyst is as follows:

[0031] (1) Synthesis of BiOBr precursor: 10 mmol of Bi(NO3)3·5H2O and 10 mmol of KBr were dissolved in 25 mL of ethylene glycol and 25 mL of deionized water, respectively, to obtain solution I and solution II. Solution II (KBr solution) was slowly dropped into solution II (Bi(NO3)3·5H2O ethylene glycol solution) under magnetic stirring. After standing, the supernatant was discarded, the mixture was washed and dried to obtain BiOBr.

[0032] (2) Preparation of Bi4TaO8Br nanosheets by molten salt method: 0.1105 g of Ta2O5 and 0.3495 g of Bi2O3 were weighed into a mortar, and 0.5 mmol of BiOBr was weighed into a mortar. The two were ground together and placed in a crucible. The mixture was heated in a muffle furnace at 10 °C min -1The temperature was raised to 700°C at a heating rate of 100 °C and maintained for 14 h. After natural cooling, the calcined product was washed with a centrifuge and dried at 60 °C to obtain Bi4TaO8Br nanosheets.

[0033] (3) 0.2 g of Bi4TaO8Br nanosheets were dispersed in anhydrous ethanol and magnetically stirred for 10 min under certain conditions. Then, 1 mmol of Fe(NO3)3·9H2O was added under stirring until dissolved. Then, the suspension was transferred into a 50 mL polyethylene-lined anti-oxidation steel autoclave for hydrothermal treatment. After naturally cooling to room temperature, the obtained product was separated, dried and collected to obtain Fe2O3-Bi4TaO8Br photo-Fenton catalyst, which was named FEOBTB-2.

[0034] Example 2

[0035] A preparation method of Fe2O3-Bi4TaO8Br photo-Fenton catalyst is as follows:

[0036] (1) Synthesis of BiOBr precursor. 10.5 mmol Bi(NO3)3·5H2O and 10.5 mmol KBr were weighed and dissolved in 25 mL ethylene glycol and 25 mL deionized water, respectively, to obtain solution I and solution II. Solution II (KBr solution) was slowly dropped into solution I (Bi(NO3)3·5H2O ethylene glycol solution) under magnetic stirring. After standing, the supernatant was discarded, washed, and dried to obtain BiOBr.

[0037] (2) Preparation of Bi4TaO8Br nanosheets by molten salt method: 0.1105 g of Ta2O5 and 0.3495 g of Bi2O3 were weighed into a mortar, and 0.6 mmol of BiOBr was weighed into a mortar. The two were ground together and placed in a crucible. The mixture was heated in a muffle furnace at 10 °C min -1 The temperature was raised to 700°C at a heating rate of 100 °C and maintained for 14 h. After natural cooling, the calcined product was washed with a centrifuge and dried at 60 °C to obtain Bi4TaO8Br nanosheets.

[0038] (3) 0.15 g of Bi4TaO8Br nanosheets were dispersed in anhydrous ethanol, and magnetically stirred for 10 minutes under certain conditions. Then, 2 mmol of Fe(NO3)3·9H2O was added under stirring until dissolved. Then, the suspension was transferred into a 50 mL polyethylene-lined anti-oxidation steel autoclave for hydrothermal treatment. After naturally cooling to room temperature, the obtained product was separated, dried, and collected to obtain Fe2O3-Bi4TaO8Br photo-Fenton catalyst. It was named FEOBTB-3.

[0039] Comparative Example 1

[0040] A preparation method of Fe2O3 catalyst, the specific preparation method is as follows:

[0041] (1) After anhydrous ethanol was magnetically stirred at 100°C at a rate of 300 r / min for 10 min, 1 mmol of Fe(NO3)3·9H2O was added under stirring until it dissolved. Then, the suspension was transferred into a 50 mL polyethylene-lined anti-oxidation steel autoclave for hydrothermal treatment at a reaction temperature of 100°C for 6 h. After naturally cooling to room temperature, the obtained product was washed three times with distilled water and anhydrous ethanol respectively, and dried at 60°C overnight and then collected to obtain a Fe2O3 catalyst.

[0042] Comparative Example 2

[0043] The preparation method of Bi4TaO8Br nanosheets in this comparative example comprises the following steps:

[0044] (1) Synthesis of BiOBr precursor: 10 mmol of Bi(NO3)3·5H2O and 10 mmol of KBr were dissolved in 25 mL of ethylene glycol and 25 mL of deionized water, respectively, to obtain solution I and solution II. Solution II (KBr solution) was slowly dropped into solution II (Bi(NO3)3·5H2O ethylene glycol solution) under magnetic stirring. After standing, the supernatant was discarded, washed, and dried to obtain BiOBr.

[0045] (2) Preparation of Bi4TaO8Br nanosheets by molten salt method: 0.1105 g of Ta2O5 and 0.3495 g of Bi2O3 were weighed into a mortar, and 0.5 mmol of BiOBr was weighed into a mortar. The two were ground together and placed in a crucible. The mixture was heated in a muffle furnace at 10 °C min -1 The temperature was raised to 700 °C at a heating rate of 100 °C and maintained for 14 h. After natural cooling, the calcined product was washed with a centrifuge and dried at 60 °C to obtain Bi4TaO8Br nanosheets, which were named BTB.

[0046] Comparative Example 3

[0047] A preparation method of Fe2O3-Bi4TaO8Br photo-Fenton catalyst is as follows:

[0048] (1) Synthesis of BiOBr precursor. 9.5 mmol Bi(NO3)3·5H2O and 9.5 mmol KBr were weighed and dissolved in 25 mL ethylene glycol and 25 mL deionized water, respectively, to obtain solution I and solution II. Solution II (KBr solution) was slowly dropped into solution II (Bi(NO3)3·5H2O ethylene glycol solution) under magnetic stirring. After standing, the supernatant was discarded, washed, and dried to obtain BiOBr.

[0049] (2) Preparation of Bi4TaO8Br nanosheets by molten salt method: 0.1105 g of Ta2O5 and 0.3495 g of Bi2O3 were weighed into a mortar, and 0.4 mmol of BiOBr was weighed into a mortar. The two were ground together and placed in a crucible. The mixture was heated in a muffle furnace at 10 °C min -1 The temperature was raised to 700°C at a heating rate of 100 °C and maintained for 14 h. After natural cooling, the calcined product was washed with a centrifuge and dried at 60 °C to obtain Bi4TaO8Br nanosheets.

[0050] (3) 0.25 g of Bi4TaO8Br nanosheets were dispersed in anhydrous ethanol and magnetically stirred for 10 min under certain conditions. Then, 0.1 mmol of Fe(NO3)3·9H2O was added under stirring until dissolved. Then, the suspension was transferred into a 50 mL polyethylene-lined anti-oxidation steel autoclave for hydrothermal treatment. After naturally cooling to room temperature, the obtained product was separated, dried and collected to obtain a Fe2O3-Bi4TaO8Br photo-Fenton catalyst, which was named FEOBTB-1.

[0051] Photo-Fenton degradation experiment

[0052] The obtained catalyst was used for photo-Fenton degradation of tetracycline (TC), and the specific steps were as follows:

[0053] (1) Take 20 mg of the catalyst and disperse it in 50 mL of tetracycline aqueous solution (tetracycline concentration is 10 mg / L), ultrasonicate it in an ultrasonic cleaner for about 5 min to make it evenly mixed, and finally stir it for 30 min in a dark environment to allow the catalyst and the target pollutant to reach an adsorption-desorption equilibrium state.

[0054] (2) A 10W white LED lamp was used to simulate the sunlight source, and (0.45 mL, 30% w / w) H2O2 solution was added and placed under the light source for irradiation to initiate the photo-Fenton reaction.

[0055] (3) Take 5 mL of solution every 10 min and measure the absorbance of tetracycline using a UV-visible spectrophotometer (UV-2600). The absorbance is set to λ=357 nm. The concentration of anti-tetracycline is further calculated based on the standard curve of absorbance and concentration.

[0056] Results Analysis

[0057] Figure 1 It is the X-ray diffraction pattern of various photo-Fenton catalysts prepared by Example 1, Example 2, Comparative Example 2 and Comparative Example 3 of the present invention. It can be seen from the figure that the characteristic peaks of Bi4TaO8Br nanosheets are consistent with the standard card, and the prepared FEOBTB composite material also has a good correspondence with the characteristic peaks of Bi4TaO8Br nanosheets, confirming the construction of the FEOBTB composite material.

[0058] Figure 2 1 is a SEM image of various photo-Fenton catalysts prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. It can be seen from the figure that Comparative Example 1 ( Figure 2 a) The sample obtained is spherical, and some are irregular small particles; a small number of Fe2O3 nanoparticles can be seen on the surface of the Bi4TaO8Br nanosheets in the sample obtained in Comparative Example 3 (Figure b), and the surface begins to become less smooth; the sample obtained in Example 2 (Figure c) has an irregular sheet structure, and some of them begin to stack, and there are fewer Fe2O3 nanoparticles on the surface; the sample obtained in Comparative Example 2 (Figure d) has a typical two-dimensional nanosheet layer morphology, and no obvious Fe2O3 nanoparticles are found. The sample obtained in Example 1 (Figures e and f) has a typical two-dimensional nanosheet layer morphology, and it can be clearly seen that Fe2O3 nanoparticles are evenly loaded on the surface of the thin sheet.

[0059] Figure 3 This is a comparison chart of the degradation performance of TC by various photo-Fenton catalysts prepared by Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. It can be seen that the removal rate of TC by Bi4TaO8Br nanosheets (BTB) within 30 minutes of photo-Fenton is only 20.04%, and the removal rate of TC by Fe2O3 is only 66.32%. The introduction of Fe2O3 can greatly improve the photo-Fenton activity of Bi4TaO8Br nanosheets, but the introduction amount of Fe2O3 will affect the catalytic effect. Among them, the photo-Fenton degradation efficiency of FEOBTB-2 sample is the highest, reaching 72.57%.

[0060] Figure 4 This is the UV-vis DRS graph of the photo-Fenton catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. It can be seen that the absorption edges of Bi4TaO8Br nanosheets (BTB) and Fe2O3 are located at 541.97nm and 779.61nm, respectively, while the absorption edge of FEOBTB-2 is significantly red-shifted compared with Bi4TaO8Br, and the absorption edge is located at 674.28nm, indicating that the light capture ability of the FEOBTB-2 photo-Fenton catalyst is enhanced.

[0061] Figure 5 As shown, multiple cycle experiments were carried out under the same conditions, and it can be seen that the FEOBTB-2 photo-Fenton catalyst has good stability. After four cycles of photo-Fenton degradation of TC experiments, the FEOBTB-2 photo-Fenton catalyst still maintained considerable performance. Its good stability makes it have certain potential for large-scale application.

[0062] Figure 6 As shown in the EIS results ( Figure 6 ), the semicircle represented by the FEBTB sample is the smallest, and the semicircle represented by the BTB sample is the largest. The results show that the FEBTB heterojunction structure can reduce the interface resistance and is beneficial to the transfer and separation of photogenerated carriers. Figure 7 All tested samples showed photoresponse characteristics under light irradiation, and the photocurrent density was FEOBTB, BTB in turn. Among them, the highest photocurrent density of FEOBTB sample showed its best photocarrier separation and migration efficiency.

Claims

1. A method for preparing a Fe2O3-Bi4TaO8Br photo-Fenton catalyst, characterized in that: The method comprises the following preparation steps: (1) Synthesis of BiOBr precursor: Weigh Bi(NO3)3·5H2O and dissolve it in ethylene glycol to obtain solution I; weigh KBr and dissolve it in deionized water to obtain solution II, drop solution II into solution I under stirring, let it stand, pour off the supernatant, wash the precipitate, and dry it to obtain BiOBr; (2) Preparing Bi4TaO8Br nanosheets by a molten salt method: Ta2O5, Bi2O3, and the BiOBr prepared in step (1) are weighed, ground together, and put into a crucible for calcination. After the calcination is completed, the calcined product is naturally cooled, washed with a centrifuge, and dried to obtain Bi4TaO8Br nanosheets; (3) Dispersing the Bi4TaO8Br nanosheets prepared in step (2) into anhydrous ethanol, stirring until the Bi4TaO8Br nanosheets and the anhydrous ethanol are fully mixed, and then adding Fe(NO3)3·9H2O while stirring until the Fe(NO3)3·9H2O is completely dissolved to obtain a suspension, subjecting the suspension to hydrothermal treatment, and naturally cooling the suspension to room temperature, separating, washing, drying, and collecting the obtained product to obtain a Fe2O3-Bi4TaO8Br photo-Fenton catalyst.

2. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: In step (1), the molar concentration of Bi(NO3)3·5H2O in solution I is 400-420 mmol / L, the molar concentration of KBr in solution II is 400-420 mmol / L, the volume ratio of solution I to solution II is 1:1, and the molar ratio of Bi(NO3)3·5H2O to KBr is 1:

1.

3. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The stirring in step (1) is magnetic stirring, the stirring speed is 250-350 r / min, and the stirring temperature is 20-100°C.

4. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The molar ratio of Ta2O5, Bi2O3 and BiOBr in step (2) is (0.2-0.3):(0.7-0.8):(0.4-0.6).

5. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The calcination conditions in step (2) are: 10°C min -1 The temperature was raised to 700 °C at a heating rate of 100 °C and maintained for 14 h.

6. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The mass molar ratio of Bi4TaO8Br nanosheets to Fe(NO3)3·9H2O in step (3) is (0.15-0.25):(1-2), in units of g:mmol.

7. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The conditions of the hydrothermal treatment in step (3) are: a holding temperature of 80 to 120° C. and a holding time of 5 to 8 hours.

8. The method for preparing the Fe2O3-Bi4TaO8Br photo-Fenton catalyst according to claim 1, characterized in that: The washing steps in step (3) are: washing thoroughly three times with distilled water and anhydrous ethanol respectively.

9. Use of the Fe2O3-Bi4TaO8Br photo-Fenton catalyst prepared by the method according to any one of claims 1 to 8 in the degradation of tetracycline in water.

Citation Information

Patent Citations

  • Photo-Fenton catalyst and preparation method thereof

    CN108212192A

  • Fe2O3 / Sr2FeTaO6-x photocatalyst, preparation method and application thereof

    CN110860295A

  • Two-dimensional bismuth ferrite-cadmium sulfide composite photo-Fenton catalyst as well as preparation method and application thereof

    CN116920881A

  • Preparation method and application of fused salt mediated CeO2 / Bi4TaO8Cl heterojunction catalyst

    CN117943068A

  • Photocatalyst structure and photocell

    WO2016136374A1

Cited By

  • Co / Bi4TaO8Cl Fenton-like catalyst as well as preparation method and application thereof

    CN120205179A

  • A Co / Bi4TaO8Cl-type Fenton catalyst and its preparation method and application

    CN120205179B

  • FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst as well as preparation method and application thereof

    CN120695853A

  • Composite type photo-fenton catalyst, preparation method thereof and application thereof in degrading rhodamine B in water

    CN122582971A